Implementing STAD cooperative learning model integrated interactive PhET simulation to enhance high school students’ learning outcomes: a case of momentum-impulse concepts - Zikry Aulia Ghiffary (Research in Physics Education, 2022)
This study aims to determine the effectiveness of STAD with the help of PhET interactive simulations in increasing student activity and learning outcomes and to find out the difference in improving student learning outcomes before and after the implementation of Student Team Achievement Division (STAD) cooperative learning with the help of PhET interactive simulations about momentum and impulse. This research was conducted because there are still many students who get unsatisfactory learning outcomes in physics subjects because students think that physics subjects are difficult to understand. One of the reasons is that learning is dominated by the teacher so students do not have the opportunity to exchange ideas. In addition, students need tools to get an overview of the material presented by the teacher. So that STAD learning with the help of interactive PhET simulation can help students to improve student learning outcomes. The research method used is a quasi-experimental design with a non-equivalent control group. Based on the Wilcoxon test, the Z value was obtained (Z=-2.532; p=0.11), and the hypothesis was that there was a difference in the improvement of student learning outcomes between those using STAD learning with the help of PhET interactive simulation and conventional learning methods.